2001
DOI: 10.1046/j.1365-2222.2001.01161.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of new sensitizations in asthmatic children monosensitized to house dust mite by specific immunotherapy. A six‐year follow‐up study.

Abstract: According to our data, SIT may prevent the onset of new sensitizations in children with respiratory symptoms monosensitized to house dust mite (HDM).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
315
6
17

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 494 publications
(344 citation statements)
references
References 22 publications
6
315
6
17
Order By: Relevance
“…It represents a realistic and potentially disease-modifying therapeutic approach for the treatment of allergic and autoimmune diseases with strong CD4 + T-cell components to their pathogenesis, such as allergic asthma (3)(4)(5). Traditional immunotherapy, using whole-protein antigens, is associated with the risk of severe allergic reactions, particularly anaphylaxis, in patients harboring allergen-reactive IgE (6,7).…”
mentioning
confidence: 99%
“…It represents a realistic and potentially disease-modifying therapeutic approach for the treatment of allergic and autoimmune diseases with strong CD4 + T-cell components to their pathogenesis, such as allergic asthma (3)(4)(5). Traditional immunotherapy, using whole-protein antigens, is associated with the risk of severe allergic reactions, particularly anaphylaxis, in patients harboring allergen-reactive IgE (6,7).…”
mentioning
confidence: 99%
“…Our search strategy identified 1378 unique publications, including over 338 peer-reviewed studies published from inception to June 30, 2015 finally retrieved , of which 18 met the inclusion criteria (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37). We excluded the Jacobsen study (38), because the outcome was reported in a subgroup of patients regardless of the treatment received, the Eifan (39) Acquistapace (40), Szepfalusi (41), and Shao (42) studies because they were not long-term studies (<3 years of treatment/follow-up).…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 shows descriptive data for the 18 systematically reviewed studies (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37). [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] and seven adult studies (31-37) included a total of 11 106 patients (1049 children, 10 057 adults), of which 8369 (75.6%) were included only in the Purello D'Ambrosio study (31). Nine of 18 studies were conducted in Italy (21,22,24,25,29,31,(33)(34)(35), four in Turkey, and (26)…”
Section: Resultsmentioning
confidence: 99%
“…First, at variance with drugs, SIT can modify the natural history of allergic disease, as recently confirmed in rigorously conducted trials such as the PAT (7), whose results are to be published soon. Second, SIT can prevent the onset of new sensitizations, as demonstrated clearly in children in several studies (8)(9)(10). Third, SIT even maintains its clinical efficacy years after discontinuation.…”
mentioning
confidence: 89%